The Role of Natural Antioxidant Products That Optimize Redox Status in the Prevention and Management of Type 2 Diabetes - Dawn S. Tuell; Evan A. Los; George A. Ford; William L. Stone (MDPI AG, 2023)
The worldwide prevalence of type 2 diabetes (T2D) and prediabetes is rapidly increasing, particularly in children, adolescents, and young adults. Oxidative stress (OxS) has emerged as a likely initiating factor in T2D. Natural antioxidant products may act to slow or prevent T2D by multiple mechanisms, i.e., (1) reducing mitochondrial oxidative stress, (2) preventing the damaging effects of lipid peroxidation, and (3) acting as essential cofactors for antioxidant enzymes. Natural antioxidant products should also be evaluated in the context of the complex physiological processes that modulate T2D-OxS such as glycemic control, postprandial OxS, the polyol pathway, high-calorie, high-fat diets, exercise, and sleep. Minimizing processes that induce chronic damaging OxS and maximizing the intake of natural antioxidant products may provide a means of preventing or slowing T2D progression. This "optimal redox" (OptRedox) approach also provides a framework in which to discuss the potential benefits of natural antioxidant products such as vitamin E, vitamin C, beta-carotene, selenium, and manganese. Although there is a consensus that early effective intervention is critical for preventing or reversing T2D progression, most research has focused on adults. It is critical, therefore, that future research include pediatric populations.